Effect of sol-gel derived TiO2 nanopowders on the mechanical and structural properties of a polymer matrix nanocomposites developed by vacuum-assisted resin transfer molding (VARTM). Issue 7 (1st April 2021) - Zahrouni, Aymen; Bendaoued, Ahlem; Salhi, Rached
Abstract: In this study, the impact of adding TiO2 nanopowders prepared by hydrothermal-assisted sol-gel method on the mechanical properties of a polyester composite reinforced by glass fibers has been investigated. The nanocomposite was fabricated using vacuum-assisted resin transfer molding (VARTM) with TiO2 nanopowders amount ranging from 0 to 7.5 wt%. The obtained results have shown that, firstly, TiO2 nanopowders are formed of anatase structure with a nanometric size in the range of 10–12 nm. Secondly, the optimum amount of TiO2 nanopowders with enhanced properties of the nanocomposite was around 5 wt%. At optimal conditions and compared to unfilled composites, the microhardness increased from 15 to 21 Hv. This result is in good correlation with the tensile modulus, ultimate tensile strength (UTS) and strain to break (SB) which increased by 14%, 83% and 246%, respectively. Including high specific strength and modulus, good fatigue resistance, a these findings may have interesting industrial applications. Graphical abstract: Image 1 Highlights: Preparation of the TiO2 nanopowders (NPs) was performed at a low temperature based on sol-gel process. Nanocomposites polyester/glass-fibers/TiO2 NPs was performed by vacuum-assisted resin transfer molding (VARTM). Dispersion of TiO2 nanofiller in polyester matrix was obtained through optimal protocol. Assessment of the effects of TiO2  nanofiller on specific mechanical properties of GFRP was performed.